Theory of planned behavior in creating disease prevention behavior - Prasetya, Hanung; Darmayanti, Aquartuti Tri; Setyorini, Yuyun (International Journal of Public Health Science (IJPHS), 2024)
Human behavior, in dealing with pandemic, becomes one of the key factors during the speed of an outbreak. In this way, individual and social responsibility are needed to determine behaviors, end the pandemic, and anticipate for the next outbreak. The purpose of this systematic review is to provide structured information about the results of applying the theory of planned behavior (TPB) in concern to create COVID-19 preventive behavior (CPB) as the case example. This systematic review was compiled by searching articles using the keywords "theory of planned behavior"[MeSH] AND COVID-19 preventive behavior. ("theory of planned behavior"[MeSH]) AND "hand disinfection"[MeSH]. "Theory of planned behavior" AND "social distancing." "Theory of planned behavior" AND "wearing mask." The search was obtained from PUBMED and Google Scholar. The 13 articles met the requirements to be reviewed qualitatively on the implementation of TPB. The results showed that TPB was effective to bring about the prevention behavior of infectious disease, such as COVID-19. Other significant aspects are intentions, norms, and behavioral control. The TPB model can be applied for health promotion in creating prevention behavior of infectious disease.